2010
DOI: 10.4314/mejs.v2i2.57669
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Praziquantel in treating <i>Schistosoma mansoni</i> infected School children in Tumuga and Waja, north Ethiopia

Abstract: Praziquantel (PZQ) is a drug of choice for treating schistosomiasis mansoni. Praziquantel was effectively used to treat schistosomiasis, but there are reports that indicate the appearance of Praziquantel resistance. The objective of this study was to determine the rate of S. mansoni infection before and after single treatment, thus to measure the efficacy of Praziquantel in treating Schistosoma mansoni infected individuals in the study area. The study utilized microscopic examination of two Kato-Katz slides fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
6
9
1
Order By: Relevance
“…The infection intensity in our study indicated low infection levels comparable with findings from Timuga and Waja from Tigray [ 36 ] and Mekelle City [ 34 ]. However, moderate infection intensities were reported from Wondo Genet [ 21 ] and Wollega [ 32 ] in Ethiopia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The infection intensity in our study indicated low infection levels comparable with findings from Timuga and Waja from Tigray [ 36 ] and Mekelle City [ 34 ]. However, moderate infection intensities were reported from Wondo Genet [ 21 ] and Wollega [ 32 ] in Ethiopia.…”
Section: Discussionsupporting
confidence: 86%
“…The efficacy of PZQ at 40 mg/kg (CR = 99.1 % and ERR = 99.9 %) in the present study is almost comparable to the reports from South Africa (CR = 100 %) [ 41 ], Sudan (CR 89–92.1 % and ERR 96.4–99.4 %) [ 42 ], Egypt (CR 73.3–92.8 %) [ 19 ] and Kenya (ERR = 92.6 % [ 43 ]. Moreover, there are two reports from Ethiopia including Tigray, Timuga and Waja (CR of 93.44 and 88.9 %) [ 36 ], Wollega (CR of 80.9 % and ERR of 99.5 %) [ 32 ], respectively, from Ethiopia at different post-treatment durations with comparable efficacy. Furthermore, the efficacy of PZQ at 40 mg/kg among students in present study is comparable with the findings from Senegal (CR = 93 % and ERR = 90 %) [ 18 ], Cameroon (CR = 95.3 %) [ 22 ], and Ethiopia (CR = 94 % and ERR = 97 % [ 44 ] with the same post-treatment duration.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study was lower than those research findings reported from different parts of Ethiopia such as from 89.9% from Saja towm, Northwest Ethiopia [7] , 85% in Zarim, 67% in Gorgora [8], 33.7% and 37.9% from northern Gonder [13,17], 73.9% from Southern Tigray [15] 81.3% from Wolita [10], 74.9% from Wondo Genet [11], 67.6% from Fincha valley Wollega [21] and 64.3% from Northwestern Tanzania [28]. This difference may be due to long endemicity of the parasites in the study area, sample size for the study, availability of the intermediate host in open water sources which the students have frequent contact with it ecological and climatic condition .…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies showed that the prevalence of S. mansoni among school children was 89.9% in Saja town [7], 85% in Zarim, 67% Gorgora [8], 23.9% of Surbs city of Mekelle [9], 81.3% from Wolita [10], 74.9% from Wondo Genet [11], 33.7% and 15.9% from Northern Gonder [12,13], 21.2% from Southern of Lake Lagano [14], 73.9% from Southern Tigray [15], 20.6% Gorgora Town [16], 37.9% from Gonder [17], 1.3% from University Gonder Community School [18] , 0.8% from Amibera district [19], 5.95% among school children of different water source users in Tigray [20] , 67.6% in Finchaa valley [21], 2.1 and 24% from Jimma [22,23]. Hygiene and play habits make children especially vulnerable to infection [3].…”
Section: Introductionmentioning
confidence: 99%
“…; Dejene et al . ). The differences in egg reduction rate and cure rate might be due to differences in brands of the drug, the time interval between treatment and evaluation of treatment efficacy, the presence of a large number of immature worms, intensity of transmission, as well as intensities of pre‐treatment egg loads, treatment failure, and possibly the presence of actual drug resistance.…”
Section: Discussionmentioning
confidence: 97%